Do teachers compensate for or compound disparities in academic achievement?. (2023) - Canales, Andrea; Maldonado, Luis
Highlights: Differential teacher benefits among socioeconomic and ethnic groups are negligible. Differences in teacher benefits by school SES and ethnic composition are substantial. Teacher seniority is associated with better academic performance but only in high SES schools. Differential teacher benefits play a small role in achievement dynamics at the individual level. At the school level, differential teacher benefits compound socioeconomic and ethnic disparities. Scholars have long discussed how schools contribute to inequality and educational opportunity. Although teacher quality is considered the most relevant aspect affecting within-school student learning factors, research on how teachers shape disparities remains limited, especially outside the US. We seek to address this gap by using matched student–teacher data and value-added models to assess whether effective teachers have the same benefits for subpopulations and in varied school contexts in Chilean secondary education. Moreover, we examine the role of experience in the heterogeneity of teacher effects. Our estimates show that differential teacher benefits do not play a significant part in achievement dynamics at the individual level. At the school level, however, differential benefits of effective teachers compound socioeconomic and ethnic disparities.